Analisis Pengaruh Leverage, Ukuran Perusahaan, Profitabilitas dan Enterprise Risk Management Risk Terhadap Kondisi Financial Distrees pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (Sub manufaktur Properties dan Real Estate Periode 2018-2021) - Chichi Chichi; Gendro Wiyono; Alfiatul Maulida (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of leverage variables, company size, profitability and Enterprise risk management on financial distress in sub-manufacturing properties and real estate companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The population used in this research is 87 companies with purposive sampling technique. The method used in this research is quantitative and the data is processed using SPSS Statistics 29. This data collection technique uses historical data from financial reports and the company's annual report. The results of this study indicate that leverage, company size, profitability and enterprise risk management have a positive and significant effect. Taken together, leverage, company size, profitability and enterprise risk management have a positive and significant effect.